Experimental Study on Seismic Strengthening of Confined Masonry Walls Using RPC - Xin Wang; Shuming Li; Zhenli Wu; Fanyang Bu; Fei Wang (Advances in Materials Science and Engineering)
Masonry structures without effective reinforcement are vulnerable to seismic excitation. An innovative strengthening technique was proposed for damaged and undamaged masonry walls. Six confined masonry units with two aspect ratios were tested under in-plane lateral cyclic loading, which consisted of two control walls, two original walls strengthened with reactive powder concrete (RPC-1), and two damaged walls repaired with RPC (RPC-2). The results of the specimens retrofitted with RPC demonstrated that the proposed technique significantly enhanced the seismic performance of masonry walls in terms of lateral strength, ductility, and energy dissipation. Furthermore, the two repaired specimens had a better distributed cracking pattern than the two strengthened specimens. The analysis of the results leads to a better understanding of the effect and mechanism of RPC seismic retrofitting for confined masonry walls.